The effects of content of training programmes on level of knowledge of personnel involved in stamp duty valuation / Siti Hasniza Rosman - Rosman, Siti Hasniza (2016)
Effective training programmes that is underpinned by integrated content holds the role to ensure that effective delivery of knowledge can be absorbed appropriately by the personnel of Valuation and Property Services Department (JPPH) that have undergone the training programmes being organized. This study is conducted to identify the effect of training programmes towards the level of knowledge of the personnel involved in stamp duty valuation. Due to its importance of the provision of the training programmes given to the personnel of an organization, hence, an investigation related to the effect of the content of the training programmes towards the knowledge of the personnel of JPPH in stamp duty valuation has been conducted. This is to identify if the content of the training programmes conducted by the National Institute of Valuation (INSPEN) towards the personnel of JPPH has ensured effectiveness and has ensured the fulfillment of the requirement of the personnel in executing their tasks effectively. This study has been conducted focusing on stamp duty involving six (6) offices of the JPPH within Klang Valley that has included the District Valuer, Valuation Officer and Assistant Valuation Officer, who are engaged in the valuation process of stamp duty, as respondents. Interview approach, pilot study, content analysis, application of Analytical Hierarchy Process (AHP) has been employed to achieve the main objective of this study. AHP which has been used in this study, is to determine the relative importance of the level of knowledge of the personnel in JPPH and also acts as the instrument that can be applied as a guide in the effort to improve the performance in the content of training programmes to fulfill the expectation and requirement of the personnel during the valuation process of the stamp duty. In summary, this study has proven that there is strong relationship between knowledge contained in the training programmes content with the level of knowledge of the personnel in stamp duty valuation.